Educational Accountability in Inclusive Schools: Exploring Perspectives and Proposing a Model for Accountability in Policy and Practice - Ahmed Bawa Kuyini (Education Sciences, 2025)
Accountability in education is an important legal, professional and ethical consideration for all teachers in their practice, as it leads to deep reflections about educational outcomes for their students. However, in respect of inclusive education, a constellation of implementation barriers has led to difficulties with understanding and ensuring accountability of outcomes for students with special educational needs (SENs). Additionally, there is very little discussion or research about accountability in special and inclusive education (SIE) in many educational systems around the world. Drawing on extant literature, this paper explores the diverse disciplinary (e.g., policy making, organisational management) understandings of accountability to illuminate the field of educational accountability. It then proposes a model for inclusive education accountability—informed by human rights—that outlines the roles, obligations of policy makers, principals, teachers, and allied professionals to enable accountable practices and outcomes for students with SENs. The proposed model suggests accountability types and obligations at different levels that can be implemented in diverse practice contexts.